Distinct regulation of bioenergetics and translation by group I mGluR and NMDAR. (29th April 2020) - Ghosh Dastidar, Sudhriti; Das Sharma, Shreya; Chakraborty, Sumita; Chattarji, Sumantra; Bhattacharya, Aditi; Muddashetty, Ravi S
Abstract: Neuronal activity is responsible for the high energy consumption in the brain. However, the cellular mechanisms draining ATP upon the arrival of a stimulus are yet to be explored systematically at the post‐synapse. Here, we provide evidence that a significant fraction of ATP is consumed upon glutamate stimulation to energize mGluR‐induced protein synthesis. We find that both mGluR and NMDAR alter protein synthesis and ATP consumption with distinct kinetics at the synaptic‐dendritic compartments. While mGluR activation leads to a rapid and sustained reduction in neuronal ATP levels, NMDAR activation has no immediate impact on the same. ATP consumption correlates inversely with the kinetics of protein synthesis for both receptors. We observe a persistent elevation in protein synthesis within 5 minutes of mGluR activation and a robust inhibition of the same within 2 minutes of NMDAR activation, assessed by the phosphorylation status of eEF2 and metabolic labeling. However, a delayed protein synthesis‐dependent ATP expenditure ensues after 15 minutes of NMDAR stimulation. We identify a central role for AMPK in the correlation between protein synthesis and ATP consumption. AMPK is dephosphorylated and inhibited upon mGluR activation, while it is phosphorylated upon NMDAR activation. Perturbing AMPK activity disrupts receptor‐specific modulations of eEF2 phosphorylation and protein synthesis. Our observations, therefore, demonstrate that the regulation of the AMPK‐eEF2 signaling axis by glutamate receptors alters neuronal protein synthesis and bioenergetics. Synopsis: Protein synthesis within cortical neurons consumes a large fraction of cellular ATP. Glutamate receptors mGlulR and NMDAR modulate AMPK‐eEF2 signaling uniquely leading to dynamic regulation of protein synthesis and bioenergetics. Protein synthesis following glutamate receptor activation is responsible for the bulk of activity‐induced ATP consumption in cortical neurons. mGluR and NMDAR regulate protein synthesis with distinct kinetics and dictate the subsequent impacts over neuronal ATP level. Dynamic modulation of AMPK and eEF2 phosphorylation is key to create unique temporal features of receptor‐specific protein synthesis and bioenergetics. Abstract : Protein synthesis within cortical neurons consumes a large fraction of cellular ATP. Glutamate receptors mGlulR and NMDAR modulate AMPK‐eEF2 signaling uniquely leading to dynamic regulation of protein synthesis and bioenergetics.